Evaluation of “Dream Herb,” Calea zacatechichi, for Nephrotoxicity Using Human Kidney Proximal Tubule Cells - Miriam E. Mossoba (Journal of Toxicology, 2016)
A recent surge in the use of dietary supplements, including herbal remedies, necessitates investigations into their safety profiles. “Dream herb,” Calea zacatechichi, has long been used in traditional folk medicine for a variety of purposes and is currently being marketed in the US for medicinal purposes, including diabetes treatment. Despite the inherent vulnerability of the renal system to xenobiotic toxicity, there is a lack of safety studies on the nephrotoxic potential of this herb. Additionally, the high frequency of diabetes-associated kidney disease makes safety screening of C. zacatechichi for safety especially important. We exposed human proximal tubule HK-2 cells to increasing doses of this herb alongside known toxicant and protectant control compounds to examine potential toxicity effects of C. zacatechichi relative to control compounds. We evaluated both cellular and mitochondrial functional changes related to toxicity of this dietary supplement and found that even at low doses evidence of cellular toxicity was significant. Moreover, these findings correlated with significantly elevated levels of nephrotoxicity biomarkers, lending further support for the need to further scrutinize the safety of this herbal dietary supplement.